2009
DOI: 10.1017/s0950268809002854
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii (Q fever) seroprevalence in cattle

Abstract: Human cases of Q fever appear to be common in Northern Ireland compared to the rest of the British Isles. The purpose of this study was to describe the seroepidemiology of Coxiella burnetii infection in cattle in Northern Ireland in terms of seroprevalence and determinants of infection. A total of 5182 animals (from a stratified systematic random sample of 273 herds) were tested with a commercial C. burnetii phase 2 IgG ELISA. A total of 6.2% of animals and 48.4% of herds tested positively. Results from a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
74
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 19 publications
19
74
1
4
Order By: Relevance
“…This agrees with previous observations in man and animals [15,[29][30][31][32]. It should be pointed out, however, that the infection can occur at any age.…”
Section: Discussionsupporting
confidence: 92%
“…This agrees with previous observations in man and animals [15,[29][30][31][32]. It should be pointed out, however, that the infection can occur at any age.…”
Section: Discussionsupporting
confidence: 92%
“…However, it was well below the range of 12.78 to 29.9% reported in the cattle from northern parts of country by other workers (Joshi et al, 1978;Vaidya et al, 2010), which may be attributed to the investigation of animals at household level, with not more than 3 cattle per house examined in the present study. On contrary, studies involving large cattle herd size with intensive farming practices were found to have a positive association with C. burnetii infection (McCaughey et al, 2010;Ryan et al, 2011;Paul et al, 2012;Agger & Paul, 2014;Boroduske et al, 2017). The positivity of a serum sample in both trans-PCR and ELISA points to an active cycling of the pathogen within the herd/animal, where the animals get infected and seroconverts frequently as described by other researchers (Freick et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the spore-like form of the agent is highly resistant to adverse environment and capable of surviving for long in soil (Evstigneeva et al, 2004). Domestic ruminants are the best known reservoir of C. burnetii and the pathogen shedding occurs primarily during the abortion or normal delivery of infected animal which can infect a large variety of animals, humans, birds, and arthropods (Parker et al, 2006;McCaughey et al, 2010). Q fever in humans is primarily transmitted through inhalation of dust contaminated with infected animal birth products or secretions, such as the placenta (Parker et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Coxiella burnetii in domestic animals, such as cattle, sheep, and goats, has been widely reported. [9][10][11][12] However, there is little detailed epidemiological data regarding the distribution and determinants of C. burnetii infection in rodents. Recent findings in Germany indicated regular sightings of wild rodents as risk factors for C. burnetii infection in humans, suggesting wild rodents as a direct source for human infection.…”
Section: Discussionmentioning
confidence: 99%